Effect of alloy elements on the weld of galvanised sheet studied by first-principles. Issue 11 (23rd July 2020) - Ma, Guohong; Yu, Xiaokang; Ye, Jia; He, Yinshui; Xiao, Yong
Abstract : To solve the problem of zinc to the weld quality of galvanised sheet, alloy elements (Cu, Nb, Y) have been added to combine with zinc to form stable compounds during welding. The structure and properties of CuZn, NbZn3 and YZn compounds were calculated by first-principles. The calculation results show that all three elements form a stable alloy with Zn. Among the alloys formed, CuZn has the best mechanical properties. MIG welding experiments of galvanised sheet were conducted to verify the effects of Cu addition on the weld seam formation. The experimental results show that the addition of Cu powder has little influence on the macro-morphology of the weld. In the centre of the weld, ferrite structure is refined and micro-hardness is improved.